The Concept of Progressive Islamic Education According to Haedar Nashir's Thoughts - Sami'in, Sami'in; Rahman, Abd (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2024)
This research aims to analyze progressive Islamic education according to Haedar Nashir's thoughts. This research attempts to examine a figure named Haedar Nashir within the Muhammadiyah Organization and his thoughts on progressive Islamic education. This study is examined holistically starting from Haedar Nashir's internal and external background, the development of his thought and his contribution to the progress of the times. Data collection techniques in this research are observation and interviews, especially those that describe and analyze phenomena, events, social activities, attitudes, beliefs, perceptions and opinions of individuals and groups. The results of this research conclude that first, Nashir views that Islamic education must be practiced holistically in the midst of a pluralistic society, so that the Muhammadiyah education system is embodied in three lines, general education (schools), madrasas and modern Islamic boarding schools. All three are directed at efforts to empower, liberate and advance society. Second, progressive Islamic education must be achieved through a holistic approach, namely the implementation of continuous education between levels, from kindergarten to higher education in a synergistic and simultaneous manner. Third, a learning orientation that optimizes all student potential, including social-emotional, intellectual, moral, creative and spiritual. Finally, Nashir explained that Islamic education is progressing in line with the pure values of Islam in building human civilization and being a blessing for the universe (ad-Din al-Hadlarah).